The impetus to Africa CDC’s mandate in curbing the rising trend of Antimicrobial Resistance (AMR) in Africa: the launch of the Africa CDC AMR surveillance network during the 8th advanced course in diagnostics (ACDx) - Takah, Noah Fongwen (Pan Afr Med J, 2017)
The rise of antimicrobial resistance is a global threat and Africa like any other developing setting is heavily affected. As one of its missions, the Africa CDC is poised to ensure this rising trend takes a diminishing route in the few years ahead. Diagnostics obviously play a pivotal role in AMR control and the advanced course in diagnostics (ACDx) has been instrumental in training critical decision makers over the past 7 years. This commentary presents an analysis of discussions and exchanges during the launch of the Africa CDC AMR surveillance network at the ACDX and the way forward for its implementation. The diagnostics priorities are also highlighted.